Early development support for children with speech and language disorders from the perspective of needs and developmental tasks - Chilman, Agata (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2021)
The purpose of the paper is to highlight the risk of child disability in the period between birth and commencement of primary education. The first part of the paper analyses differences in defining the target group of early development support and intervention, a distinction is made between disability and the risk of disability. The paper describes selected concepts of early developmental support and traditional psychological concepts regarding human development. The second part of the paper presents concepts of speech and language disorders in children. The paper discusses the dependence between linguistic competencies and global development of a child and the problem of early development diagnosis and evaluation of cognitive functions, listing the methods and tools used to examine young children.